Penguatan Jiwa Kewirausahaan untuk Mendukung Kontinuitas Produk Olahan Nanas melalui Penerapan Teknologi Tepat Guna pada KWT Barokah Lumintu Desa Siwarak - Dewanti Risa Utami; Lutfi Zulkifli; Malinda Aptika Rachmah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The Barokah Lumintu Women Farmers Group (KWT) in Siwarak Village has great potential in processing pineapple as the village's leading commodity. However, the processing activities carried out are still simple, not yet standardized, and not yet oriented towards production continuity and market needs. This community service activity aims to strengthen the entrepreneurial spirit of KWT members and increase the capacity and continuity of pineapple processing products through the application of appropriate technology. The implementation methods include entrepreneurship training, technical training in pineapple processing, assistance in the application of appropriate technology, and strengthening of production and marketing management. The results of the activities show an increase in the knowledge and skills of KWT members in pineapple processing, an increase in production process efficiency, and the growth of a more market-oriented entrepreneurial awareness. This program is expected to encourage the sustainability of the pineapple processing business and increase the economic independence of the members of KWT Barokah Lumintu.